A modified linear capacitive displacement transducer for any range - Saikat Kumar Bera; Moumita Chakraborty; Pradip Kumar Sadhu (Heliyon)
–In the present paper, a modified linear capacitive displacement transducer is developed, where the measurement errors and non-linearity errors due to the various effects such as the effect of the change of atmospheric parameters, the effect of parasitic fringe capacitance, the effect of stray capacitance, the effect of parallel position shifting of the sensing plates, etc. are minimized, and the output is linearly related with displacement for any range. The transducer consists of a sensing capacitor and a similar reference capacitor, each of which has a noninductive double layer short-circuited winding wound on an insulating uniform hollow cylinder. The sensing cylinder has a thin circular conducting disk, which is easily displaceable by the moving object along the inside walls of the cylinder from the outside by means of a thin conducting disk rod attached to the central position of the disk. The reference cylinder has a similar disk with a disk rod fixed at the reference zero position. The transducer circuit measures the difference of the combined cylindrical-perpendicular plate capacitances between the short-circuited terminal of vertical noninductive winding and the horizontal conducting disk of the two capacitors and gives an output that is found to be linearly related with displacement for the entire length of the sensing cylinder. The measurement is free from the non-linearity error for any range because the factors producing nonlinearity are similar for the two capacitors and tend to cancel each other. The derived characteristic equations are supported by the experimental results with very good accuracy and repeatability.